Dampak Implementasi Sistem Informasi Gampong (SIGAP) pada Digitalisasi Administrasi Desa dalam Konsep Smart Village Initiative di Gampong Luthu Lamweu, Aceh Besar - Al Bahri; Safrizal Razali; Maimun; Aulia Rahman; Sayed Muchallil; Hubbul Walidainy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
A quantitative descriptive approach with a retrospective pre-test design was used to assess changes in community perceptions through a Likert-scale questionnaire covering seven key indicators, including service speed, data accessibility, and digital literacy. Results show significant improvements across all indicators, with the highest gains in data access (21%) and administrative transparency (20%). These outcomes highlight SIGAP’s potential to strengthen technology-driven governance and foster community engagement in smart village development. The findings offer practical implications for rural digital transformation and the implementation of information systems in other local contexts.